Histological analysis of fat grafting with platelet‐rich plasma for diabetic foot ulcers—A randomised controlled trial. Issue 2 (24th June 2021) - Nolan, Grant Switzer; Smith, Oliver John; Heavey, Susan; Jell, Gavin; Mosahebi, Afshin
Abstract: Diabetic foot ulcers are often unresponsive to conventional therapy and are a leading cause of amputation. Animal studies have shown stem cells and growth factors can accelerate wound healing. Adipose‐derived stem cells are found in fat grafts and mixing them with platelet‐rich plasma (PRP) may improve graft survival. This study aimed to establish the histological changes when diabetic foot ulcers are treated with fat grafts and PRP. A three‐armed RCT was undertaken of 18 diabetic foot ulcer patients: fat grafting; fat grafting with PRP; and routine podiatry care. Biopsies were obtained at week 0, 1, and 4, and underwent quantitative histology/immunohistochemistry (H&E, CD31, and Ki67). Treatment with fat and PRP increased mean microvessel density at 1 week to 1645 (SD 96) microvessels/mm 2 (+32%‐45% to other arms, P = .035). PRP appeared to increase vascularity surrounding fat grafts, and histology suggested PRP may enhance fat graft survival. There was no clinical difference between arms. This study demonstrates PRP with fat grafts increased neovascularisation and graft survival in diabetic foot ulcers. The histology was not, however, correlated with wound healing time. Future studies should consider using apoptosis markers and fluorescent labelling to ascertain if enhanced fat graft survival is due to proliferation or reduced apoptosis. Trial registration NCT03085550.